THE STUDY OF ANTIOXIDANTS TO EVALUATE THE HEALING EFFECTS OF PUNICA GRANATUM PEEL ON ACETIC ACID-INDUCED COLITIS IN CHARLES-FOSTER ALBINO RATS - VERMA, ARPIT; BHADKARIYA, ANAND; SHARMA, SUPRIYA; TOSHI, NIKITA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The study aims to analyze the effect of 50% ethanolic extract of the dried Punica granatum peel (PGE) on the healing of acetic- acid-induced colitis in rats. Methods: Colitis was induced in rats using 50% acetic acid and then PGE extract was administered by oral route daily for 14 days to those rats. Optimal healing was observed by the administration of a 100 mg/kg dose of PGE extract. Effectiveness of the above-mentioned dosage of PGE, biochemical parameters namely- antioxidants-superoxide dismutase and reduced glutathione were studied on 18 h fasting rats on the 15th day of the experiment. Results: The results were suggestive of the healing properties of PGE extract by reduction of the inflammation and mucosal damage in the colon of those rats. The effect was established by the levels of antioxidants that indicate healing of the mucosal damage. The safety of extract was established by the effective administration of 10 times the therapeutic dose, that is, 1000 mg/kg dosage of the PGE extract with no noticeable adverse effects or side effects related to autonomic nervous system or central nervous system. Conclusion: PGE extract was found to be effective in healing mucosal damage due to colitis by controlling the infection and reducing the inflammation.